Determinants of Employee Electricity Saving Behavior in Small Firms: The Role of Benefits and Leadership - Olawale Fatoki (Energies, 2022)
The emission of carbon dioxide and other greenhouse gases through electricity consumption by firms is one of the significant drivers of climate change. The performance of a firm’s environmental programme is to a large extent dependent on employee behaviour. Drawing on the Theory of Planned Behaviour (TPB), the study tested a theoretical model that incorporates benefits and leadership as antecedents of attitude towards electricity saving by the employees of small firms in the hospitality sector. The effects of five benefits (intrinsic, extrinsic, organisational, social, and environmental) and two leadership factors (leadership behaviour and leadership support) were examined. Investigating the antecedents of TPB constructs can help in understanding the process through which the constructs are associated with intention. In addition, the moderating effect of green psychological climate in the relationship between intention and electricity saving behaviour was examined. The study used the quantitative research design, and the cross-sectional survey method was used for data collection. The hypotheses of the study were tested using the Partial Least Square Structural Equation modelling (PLS SEM). The results of the empirical study indicated that intrinsic, organisational, social, and environmental benefits are positively related to attitudes towards electricity saving. In addition, the effects of leadership behaviour and support are significant. Furthermore, green psychological climate moderates the relationship between intention and electricity saving behaviour. Recommendations to improve employees’ electricity saving behaviour are suggested.